Inorganic Phosphate Effect in a Hydrogen Peroxide-based Bleaching Agent: Physicochemical, Mechanical, and Morphological Properties of Dental Enamel - Garcia, K. G.; Nunes, G. P. [UNESP]; Delbem, Acb [UNESP]; Dos Santos, P. H. [UNESP]; Fernandes, Glp [UNESP]; Robles, H. F.; Lemos, Pbb; Danelon, M. [UNESP] (Operative Dentistry, 2024)
OBJECTIVES: This in vitro study aimed to assess the impact of incorporating calcium glycerophosphate (CaGP) and sodium fluoride (NaF) in addition to 35% hydrogen peroxide concerning the enamel mechanical and morphological properties. METHODS: Specimens of bovine enamel were chosen based on their initial surface hardness (SHi) and subsequently divided into five gel groups (n=12): 1) 35% Hydrogen Peroxide (HP) Gel; 2) HP + 0.1% NaF Gel (HP/NaF); 3) HP + 0.25% CaGP Gel (HP/CaGP); 4) HP + 0.1% NaF + 0.25% CaGP Gel (HP/NaF/CaGP) and 5) HP Blue 35% Gel (HP Blue). The bleaching gels were applied thrice, for 40 min, at intervals of 7 days each. After 21 days, the final surface hardness (SHf), integrated hardness (IH), Polydispersity Index (PdI) and Zeta Potential (Zp), surface roughness (Ra, after and before), and surface/structural analysis by Scanning Electron Microscopy (SEM) were determined. The data were submitted to ANOVA (one-way and two-way) followed by the Student-Newman-Keuls test (α=0.05). RESULTS: The addition of NaF to HP reduced demineralization by 11.5% in relation to HP (p<0.05). The NaF/CaGP association reduction is 22.8 and 20% higher in comparison to HP/NaF/CaGP and HP Blue, respectively. The IH when the PH/NaF/CaGP bleaching gel was applied, was 14% higher compared to HP and HP Blue groups. CONCLUSIONS: It can be concluded that the association of NaF and CaGP with the 35% hydrogen peroxide gel (HP/NaF/CaGP) significantly changed tooth enamel demineralization in terms of surface, depth, roughness, and enamel morphology.